RF front end design - Rahim, Kamal (UTM, 1999)
Microstrip transmission line is used over the frequency range from 1 GHz to 40 GHz. The circuit dimensions at higher frequency are very small and circuit losses become high. In practice microstrip is used extensively over 2 to 12 GHz range where small compact circuits, suitable for the inclusion of active devices. The circuits using microstrip have several advantages such as light weight, small size, low cost as compared to conventional microwave waveguide. This project involves the design and fabrication of RF subsystems using microstrip line such as low pass filter, bandpass filter, power divider and hybrid line coupler. The performance of various design is analyse through simulation and measurement.